Jarum Sikenang (Semarang Keroncong Musicians Network) 2022: A Program for Promoting Cultural Advancement In Semarang - Ibnu Amar Muchsin (Jurnal Seni Musik, 2024)
Keroncong is a distinctive Indonesian music genre regarded as a cultural heritage that needs preservation. However, keroncong music faces the threat of extinction, a concern shared by musicians, music enthusiasts, cultural experts, and government officials. This study aimed to identify and explain the establishment of “JARUM SIKENANG" program as an effort to promote cultural advancement through the preservation of keroncong music to boost tourism in Semarang City. This study employed qualitative method, with data collected through document studies. The data analysis followed the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings include expanding public access to keroncong music (development aspect), organizing workshops to improve the quality of keroncong musicians (mentoring aspect), promoting keroncong music to the wider community (protection aspect), involving keroncong musicians in various tourism events, and partnering with sponsors to improve the welfare of keroncong musicians in Semarang City (utilization aspect).